Răspuns :
a) 5x+3x-18=7x+13
8x-7x=13+18
x=31
b) 6x+4x-24=9x+21
10x-9x=21+24
x=45
c) 5x-35-2x=x-41
3x-x= - 41+35
2x= - 6
x= -3
d) 7x-63-4x=x-39
3x-x= - 39+63
2x=24
x=12
8x-7x=13+18
x=31
b) 6x+4x-24=9x+21
10x-9x=21+24
x=45
c) 5x-35-2x=x-41
3x-x= - 41+35
2x= - 6
x= -3
d) 7x-63-4x=x-39
3x-x= - 39+63
2x=24
x=12
a) 5x+3x-18=7x+13
8x-7x=13+18
x=31
b) 6x+4x-32=9x+21
10x-9x=21+32
x=53
c) 5x-35-2x=x-41
5x-3x=-41+35
2x=-6
x=-3
d) 7x-63-4x=x-39
2x=-39+63
x=24/2
x=12
8x-7x=13+18
x=31
b) 6x+4x-32=9x+21
10x-9x=21+32
x=53
c) 5x-35-2x=x-41
5x-3x=-41+35
2x=-6
x=-3
d) 7x-63-4x=x-39
2x=-39+63
x=24/2
x=12